(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
According to the decree of the President of the Republic of Uzbekistan on 29th July, 2021, number PD-5202, about actions on carrying out the special resolution "About announcing the Aral Sea area as the territory of ecological innovations and technologies" of the main assembly of the organization of the United Nations on 18th May, 2021, plans were accepted about producing agricultural crops, which were planted on the main and intermediate fields, cotton, rice, vegetables, cucurbits crops, potato, fodder, tubers, annual plants, alfalfa, maize, corn, tobacco, leguminous crops, also, other crops which are planted in the method "garlic planting". In this decree: 1. It should be received as an information that, in the paragraph of the special resolution "About announcing the Aral Sea area as the territory of ecological innovations and technologies", in order to sow cotton, rice, maize, corn and feed farm animals on 2,5 thousand hectares field of the Republic of Karakalpakstan, appointments were made about modernization of experimenting laboratories (food, agriculture, electro techniques, light industry) and applying logistic service on delivering samples to the laboratory